Kinetics of hydroformylation of 1-decene using carbon-supported ossified HRh(CO)(TPPTS)(3) catalyst - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2019)
The kinetics of hydroformylation of 1-decene has been investigated using a carbon-supported ossified HRh(CO)(TPPTS)(3)/Ba catalyst in a temperature range of 343-363 K. The effect of concentration of 1-decene, catalyst loading, partial pressure of H-2 and CO, and stirring speed on the reaction rate has been investigated. A first-order dependence was observed for catalyst concentration and hydrogen partial pressure. The rate showed a typical case of substrate inhibition for high 1-decene concentration. The rate varied with a linear dependence on P-CO up to a CO partial pressure of 5-6 MPa in contrast to the general trends; for most of the rhodium-phosphine catalyzed hydroformylation reactions, severe inhibition of rate is observed with an increase in CO pressure. A rate equation has been proposed, which was found to be in good agreement with the observed rate data within the limit of experimental errors. The kinetic parameters and activation energy values have been reported.
Keywords: 1-decene; Hydroformylation; kinetics; ossification; supported ossified

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Synthesis, characterization and catalytic study of mesoporous carbon materials prepared via mesoporous silica using non-surfactant templating agents - Pagar, Nitin S.; Karandikar, Prashant R.; Chandwadkar, Asha J.; Deshpande, Raj M. (Journal of Porous Materials, 2020)
Mesostructured silica materials with surface area in the range of similar to 700-900 m(2)/g have been prepared using hydroxy-carboxylic acid compounds such as tartaric acid, malic acid and citric acid (low cost non-surfactant template/pore forming agents) and tetraethylorthosilicate (TEOS) as silica source by sol-gel reaction. The templates were removed by either soxhlet extraction or calcination method. Mesoporous carbon molecular sieves were then prepared by carbonizing sucrose inside the pores of the above prepared mesoporous silica using sulfuric acid as a catalyst. The materials were characterized by FTIR spectroscopy, powder X-ray diffraction (XRD), N-2-sorption studies, microanalysis, thermal analysis and transmission electron microscopy (TEM). The resulting carbon material shows relatively higher surface area (similar to 1100 m(2)/g), narrow pore size distribution and pore diameter of 4-5 nm. The mesoporosity of carbon material arises from interconnecting channels arrangements of mesoporous silica template. The mesoporous carbon material was used as a support for the immobilization of rhodium complex [HRhCO(TPPTS)(3)] by ossification method. The prepared catalyst has been tested for the hydroformylation of higher olefins. The activity of the catalyst was improved by 20-30% as compared to the catalyst prepared from a conventional activated carbon support.
Keywords: Carbonization; Hydroformylation; Immobilization; Low cost templates; mesoporous carbon; Mesoporous silica

Kinetics of 1-decene hydroformylation in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of a cosolvent - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2021)
The kinetics of hydroformylation of 1-decene has been studied in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of N-methyl pyrrolidone as a cosolvent at 383-403 K. The rate was found to be first order, with concentrations of catalyst and olefin and partial order, with concentrations of hydrogen in the liquid phase. The plot of rate versus excess ligand and CO concentrations passed through maxima, indicating negative order dependence at higher concentrations. These trends have been interpreted based on the established hydroformylation mechanism. High selectivity towards the linear aldehyde was maintained (n: iso ratio > 30). An empirical rate equation has been proposed which was found to be in good agreement with the observed rate data within the experimental error. The activation energy was evaluated to be 74.76 kJ/mol.
Keywords: 1‐ aqueous‐ biphasic; cosolvent; decene; Hydroformylation; kinetics; rh‐ sulfoxantphos

Kinetic investigation on palladium-catalyzed carbonylation of allyl alcohol - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2025)
Palladium-catalyzed carbonylation of allyl alcohol to 3-butenoic acid has been investigated. A significant effect of halide promoters, p-tolylsulfonic acid (TsOH), water, solvents, and PPh3 concentration activity and selectivity has been studied. Detailed kinetics of this reaction was investigated in a temperature range of 363-383 K. The influence of parameters such as stirring speed, allyl alcohol, catalyst, benzyltriethylammonium chloride (BTEAC), TsOH concentrations, and CO partial pressures on the activity and selectivity has been studied. An empirical rate equation was suggested and found to be fairly consistent with observed rate data. In addition, the activation energy and kinetic parameters were evaluated.
Keywords: allyl alcohol; Carbonylation; halide promoters; kinetics; Mechanism; Palladium